2022
DOI: 10.3389/fimmu.2022.995886
|View full text |Cite
|
Sign up to set email alerts
|

Comparable bidirectional neutrophil immune dysregulation between Kawasaki disease and severe COVID-19

Abstract: Kawasaki disease (KD), a multisystem inflammatory syndrome that occurs in children, and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 or COVID-19) may share some overlapping mechanisms. The purpose of this study was to analyze the differences in single-cell RNA sequencing between KD and COVID-19. We performed single-cell RNA sequencing in KD patients (within 24 hours before IVIG treatment) and age-matched fever controls. The single-cell RNA sequencing data of COVID-19, influenza, and health contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It is reported that the number of neutrophils is considered as a clinical marker related to acute respiratory distress syndrome in COVID-19 patients ( Oishi et al, 2022 ). Moreover, one study has also demonstrated that similar neutrophilic dysregulation occurs in severe COVID-19 and KD two pronounced hyperinflammatory states, which plays a crucial role in the overactivation and defective aging program of granulocytes ( Chen K D et al, 2022 ). In short, based on the results of the KEGG enrichment analysis, we could conclude that these genes were more likely to be involved in neutrophil-related biological activities.…”
Section: Discussionmentioning
confidence: 98%
“…It is reported that the number of neutrophils is considered as a clinical marker related to acute respiratory distress syndrome in COVID-19 patients ( Oishi et al, 2022 ). Moreover, one study has also demonstrated that similar neutrophilic dysregulation occurs in severe COVID-19 and KD two pronounced hyperinflammatory states, which plays a crucial role in the overactivation and defective aging program of granulocytes ( Chen K D et al, 2022 ). In short, based on the results of the KEGG enrichment analysis, we could conclude that these genes were more likely to be involved in neutrophil-related biological activities.…”
Section: Discussionmentioning
confidence: 98%
“…High-dose IVIG therapy and aspirin are commonly used treatments to reduce inflammation and prevent complications of CALs. However, even with treatment, some children may still develop CALs, highlighting the importance of close monitoring and other potential anti-inflammation agents [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the case of SLE, it has been shown that neutrophils can contribute to an increase in BAFF and a strengthening of the autoimmune process. In the case of MIS-C, hallmarked by marked neutrophilia and disturbed neutrophil functionalities [ 25 , 26 ], a similar parallel might exist and contribute to the induction of autoimmunity [ 27 ].…”
Section: Discussionmentioning
confidence: 99%